Respuesta :
∙•❁ Okay time to solve this Step-By-Step.❁•∙
16−2n−5+8n=65
∙•❁ So the first part we need to Simplify both sides of this equation, so:
16−2n−5+8n=65
∙•❁ We are going to simplify this Step-By-Step.
16−2n−5+8n=65
16+−2n+−5+8n=65
∙•❁ Combine like terms:
(−2n+8n)+(16+−5)=65
6n+11=65
6n+11=65
∙•❁ Now subtract 11 from both sides.
6n+11−11=65−11
6n=54
∙•❁ Now divide both sides by 6 and you'll get your answer:
6n/6=54/6
∙•❁ Your final answer is:
n=9
∙•❁I hope this helps!❁•∙
16−2n−5+8n=65
∙•❁ So the first part we need to Simplify both sides of this equation, so:
16−2n−5+8n=65
∙•❁ We are going to simplify this Step-By-Step.
16−2n−5+8n=65
16+−2n+−5+8n=65
∙•❁ Combine like terms:
(−2n+8n)+(16+−5)=65
6n+11=65
6n+11=65
∙•❁ Now subtract 11 from both sides.
6n+11−11=65−11
6n=54
∙•❁ Now divide both sides by 6 and you'll get your answer:
6n/6=54/6
∙•❁ Your final answer is:
n=9
∙•❁I hope this helps!❁•∙